An ethical advantage of autistic employees in the workplace - Hartman, Lorne; Hartman, Braxton (Frontiers in Psychology, 2024)
Previous research indicates that autistic employees are less susceptible to the bystander effect than nonautistic employees. This paper considers whether these differences are moderated by "moral disengagement," a set of interrelated cognitive mechanisms that allow people to make unethical decisions by deactivating moral self-regulatory processes. Thirty-three autistic employees and thirty-four nonautistic employees completed an on-line survey to determine whether differences between autistic and nonautistic employees with regards to (1) likelihood they would voice concerns about organizational dysfunctions, and (2) degree to which they were influenced by the presence of others when deciding to intervene, are moderated by individual differences in moral disengagement. As predicted, autistic participants scored lower on moral disengagement than nonautistic participants. In terms of the moderating effects of moral disengagement, the results are mixed. Although moral disengagement reduced intervention likelihood, there was not a difference between autistic and nonautistic employees in the degree to which intervention likelihood was changed by an individual's level of moral disengagement.However, there was a difference between autistic and nonautistic employees in the extent to which acknowledging the influence of others was affected by moral disengagement. These findings suggest that autistic adults are not just more likely to intervene when they witness dysfunction or misconduct in an organizational context; they are also less likely to engage in unethical behavior in general due to lower levels of moral disengagement. The reduced susceptibility to the bystander effect evidenced by autistic